Meal management practices of newly married couples - Rosario, Charisse Grace Dy.; Trio, Consuelo Q. (2007., 2007)
This study examined the meal management practices of newly married couples, specifically on the aspects of meal planning, food budgeting, food purchasing, food preparation and cooking. The research looked at the division of meal management tasks between the husband and the wife, the factors that couples considered in managing their meals, and the problems they have encountered. Forty-five couples who were married for the past five years participated in the research. They answered a survey questionnaire that solicited information about their meal management practices and the problems that they encountered in performing meal management activities. The results showed that for the majority of the couples, the tasks of menu planning, food budgeting and market list preparation are mostly performed by the wife. On the other hand, the activities of food purchasing and meal preparation were generally shared between the wife and the husband. Food budget and nutrient content were the main factors that newly married couples consider when planning the menu, purchasing food and preparing meals. Other factors that couples considered include food preference of family members and variety of meals. Food budget was also the main source of problem in menu planning and purchasing. Conversely, insufficient cooking skills seem to be the main problem with regards to meal preparation. Overall, the study showed that it is still the wives who played the key role in the meal management activities of the family. The primary factor considered in meal management was food budget, which was also the main source of meal management problems. Recommendations for future research are provided at the end of the paper.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Meal management; Married people -- Philippines